Pengembangan Modul Pembelajaran IPAS Berbasis Scientific Learning pada Siswa Kelas IV SDN 1 Suwangi Timur - Mijahamuddin Alwi; Arif Rahman Hakim; Yuliana Yuliana (Jurnal Pelita: Jurnal Pembelajaran IPA Terpadu, 2025)
This study was motivated by the limitations of conventional science modules, which are less contextual and have not effectively enhanced students’ motivation, engagement, and critical thinking skills. The purpose of this study is to develop a Science Learning Module (IPAS) based on Scientific Learning for fourth-grade students at SDN 1 Suwangi Timur. The research employed a R&D method using a simplified 4D model consisting of three stages: definition, design, and development. Expert validation data were analyzed quantitatively using a Likert scale and converted into qualitative data to assess the module's feasibility, while field trial data were analyzed descriptively to evaluate student activity and responses, providing an overview of the effectiveness of the Scientific learning-based module. The study involved 21 fourth-grade students at SDN 1 Suwangi Timur. The module was developed using expert validation sheets and student response questionnaires. The results of the material expert validation obtained a score of 63 (range 51 < X ? 63), categorized as “good,” while the display expert validation scored 73 (range 73 < X ? 54.58), categorized as “very good.” Student response questionnaires regarding the effectiveness of the developed learning module showed an average score of 88.7% (X > 54.58), categorized as “very good.” Therefore, it can be concluded that the development of the Scientific learning-based science module for fourth-grade students at SDN 1 Suwangi Timur is highly feasible and effective for use in the learning process.